On some novel bright, dark and optical solitons to the cubic-quintic nonlinear non-paraxial pulse propagation model - Tariq, Kalim U.; Khater, Mostafa M. A.; İnç, Mustafa (Springer, 2021)
In this article, the modified Khater method is utilized to extract new analytical solutions to the cubic-quintic nonlinear non-paraxial pulse propagation model in a planar waveguide with Kerr nonlinearity, fifth-order nonlinearity, and spatiality dispersion due to non-paraxial effects. As a result, a variety of some new exact solutions are observed. Moreover, the three-dimensional shapes are visualized with the aid of the latest scientific tools.
Keywords: Alytical solutions; Schordinger model; Optical fiber; Soliton waves; Computational analysis; Modified Khater method